Mu’adah Shalat Jum’at Di Pesantren Balerante - Aah Syafaah; Salma Mumtazah; Hasbiyallah Hasbiyallah (Jurnal Tamaddun, 2023)
This study aims to discuss an interesting issue at the Balerante Islamic Boarding School. Related to the mu'adah of Friday prayers found in the book creatice SabilIl Huda Fi al-Jumuah Wa Fi al-Raddi ‘Ala Man Mana’a al-Mu’adah by ‘Ulama kyai Muhammad Jauhar Arifin. Where Kyai Jauhar is the grandson of the founder of the Balerante Islamic Boarding School, Kyai Muhammad Romli. The scientific Sanad obtained by Kyai Jauhar was continued in Makkah to Sheikh Mahfudz Al-Tarmasi. This writing aims to find out how the laws made by ‘Ulama Jauhar related to Friday Prayer Mu'adah accompanied by evidence/reasons accompanying it. This research method includes five important aspects, namely approaches and methods, types of data and sources, data collection techniques, data analysis techniques, and time and place of research. The writing technique is in the form of descriptive analysis based on literature review and field research. According to ‘Ulama Jauhar the law of mu'adah is divided into 3, namely prohibited, obligatory and sunnah (fadhoilul a'mal). With various argumentation which accompanies it based on the provisions of the Islamic Shari'ah that apply according to the Shafii’s Islamic legal school.